CHANGES IN SERUM INTERLEUKIN-8 AND AUTOANTIBODY LEVELS IN PATIENTS WITH AUTOIMMUNE THYROIDITIS - Rahimova, R.R.; Efendiyev, A.M.; Mehdiyev, L.; Dashdamirova, G.S.; Guliyeva, S.R.; Rzayeva, F.F. (World of Medicine and Biology, 2024)
Hashimoto’s disease is the most common autoimmune disease involving the thyroid gland. It is caused by the destruction of thyroid cells, which is mediated by humoral and cellular immunity disbalance. Thyroid hormones play a critical role in regulating metabolism, homeostasis, and the immune response. This study examines the role of interleukin-8 and different types of autoantibodies in patients with autoimmune thyroiditis to identify any significant associations between the cytokine and autoantibodies. In a study involving 170 patients with Hashimoto’s disease (64 men and 106 women aged 18 to 64 years) was carried out a comprehensive examination of the proinflammatory cytokine interleukin-8, organ-specific antithyroglobulin, anti-thyroid peroxidase and organ-non-specific anti-DNA antibodies. The control group comprised 65 people without thyroid pathologies and other autoimmune diseases aged 20 to 65 (26 men and 39 women). The study demonstrated that disease severity is associated with changes in the levels of interleukin-8, organ-specific antibodies, and antibodies to double-stranded DNA.